Electrochemical oxidation behavior of some hazardous phenolic compounds in acidic solution - H. Nady; M.M. El-Rabiei; G.M. Abd El-Hafez (Egyptian Journal of Petroleum)
The electrochemical oxidation of phenol, resorcinol and pyrogallol was investigated in sulfuric acid solution. Cyclic voltammetry and electrochemical impedance spectroscopy, EIS, were used. The mechanism of the electrochemical oxidation process was proposed and discussed. The process includes a selective oxidation and PtOx formation. EIS measurements were carried out to further examine the reaction kinetics involved in the phenolic compounds electro-oxidation. The EIS responses were found to be strongly dependent on electrode potentials. The result showed the presence of an oxidation peak in the region around 1 V vs SCE to all conditions evaluated. In cyclic voltammetric experiments a gradual decrease of the oxidation peak with the number of cycles was observed. This suggests the deactivation or blockage of the electrode surface by the adsorption of substances and/or phenoxy radical polymerization.